Effect of cerium content on textural and hydrodesulfurization performance for dibenzothiophene over a bulk Ni2P catalyst. (February 2019) - Yu, Yunwu; Liang, Lianjie; Xu, Changwei; Dai, Yubo; Pan, Wenhao; Ding, Zhaoyang; Liu, Yunxue
A series of ceria promoted Ni2 P catalysts were prepared and evaluated in dibenzothiophene hydrodesulfurization steam. These catalysts were characterized by X-ray diffraction, N2 adsorption–desorption, CO chemisorptions, and X-ray photoelectron spectroscopy. The results showed that the addition of ceria into the bulk Ni2 P catalyst was conducive to the formation of the Ni2 P phase and contributed to a higher surface area, leading to a better dispersion and smaller crystallite size of Ni2 P particles. The Cex Ni2 P catalysts showed higher dibenzothiophene hydrodesulfurization activity than Ni2 P catalyst and the Ce0.09 Ni2 P catalyst showed the highest dibenzothiophene hydrodesulfurization activity. The Ce0.09 Ni2 P catalyst showed a dibenzothiophene hydrodesulfurization conversion of 94.5% at the reaction conditions of 320°C, 4.0 MPa, a H2 /oil ratio of 500 (V/V), and a weight hourly space velocity of 8.0 h −1 . The dibenzothiophene was mainly transformed through desulfurization pathway.